Doctor Who. The Daleks. [videorecording (DVD)] - Eccleston, Christopher; Tennant, David, 1971-; Smith, Matt, 1982-; Capaldi, Peter (BBC, 2015)
The hideous mutant creatures and the most feared race in the entire universe, are about to make life miserable for the Time Lord and delightful for Whovians. Take a trip through time and space as the Doctor and his companions battle a deadly enemy in the amazing collection of iconic Doctor Who episodes! Includes an adventure with each of the modern Doctors.